Analisis Prinsip-Prinsip Environmental, Social And Governance (ESG) Pada Operasional BSI Stabat Kh Zainul Arifin - Aini, Bunga Quratul (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to evaluate the implementation of Environmental, Social and Governance (ESG) principles in operations, opportunities and challenges that affect BSI KCP Stabat KH Zainul Arifin. This article is qualitative research and uses secondary data collected through library materials as well as primary data obtained through direct interviews with BSI KCP Stabat KH Zainul Arifin. The study findings explain that BSI Stabat KH Zainul Arifin has systematically implemented ESG principles in its operations and obtained opportunities to increase customer trust in a sustainable economy. However, there are challenges such as ensuring compliance with sharia principles, measurement, ESG performance reporting, education and awareness of BSI Stabat KH Zainul Arifin. This study provides insight into how banks can understand, implement and measure their ESG performance, and can be used as a basis for recommending improvements in achieving long-term sustainability and maintaining a good reputation.